Semiotic Interpretation of Designing Poster Advertisements for Local Product Tangkuban Chocolate as a Promotional Media - Kusumawati, Desiana Nur Indra; Kusumah, Wisnu Indra; T, R. Widyo Wibisono; Dewa Tirta Kencana (Sean Institute, 2025)
The problem in promoting local MSME products is the lack of strong and meaningful visual branding, especially for regional specialty products. This study aims to describe the meaning of Roland Barthes' Semiotics and the function of poster design as an advertising medium for Proster Local products with Tangkuban Coklat 62 Branding, a typical West Java or Sundanese chocolate product. The poster raises local cultural values through visuals of the legendary figure Sangkuriang, Mount Tangkuban Parahu, and a packaging concept that is integrated with the identity in the form of a Sundanese Legend. The method used is a qualitative approach with Roland Barthes' semiotic analysis to reveal the visual and verbal messages in the poster. The results of the study show that poster design is able to be an effective visual communication tool in promoting local culture-based MSME products. Where it can be concluded that the visual elevation of local culture can be a branding that has a Meaning to make the Promotion of a local chocolate product attractive.